Polityka turystyczna Czech, Polski i Niemiec a możliwości rozwoju współpracy transgranicznej w zakresie turystyki na pograniczu polsko-czesko-niemieckim - Gryszel, Piotr; Jaremen, Daria E.; Nawrocka, Elżbieta (Czech, Polish and German Tourist Policy vs. Opportunities for Cross-Border Cooperation in Tourism in Polish-Czech-German Border Areas, 2005)
In spite of the existence of the Neisse-Nisa-Nysa Euroregion along Polish-Czech-German border areas for over ten years and the carried out cooperation within the framework of tourism development in this area, an extremely important element of tourist economy development becomes the properly created tourist policy. Such policy, however, is the domain of top govemmental spheres, that is why the influence of the Euroregion on its creation by the particular countries is only of an indirect nature. In cross-border cooperation, at the Polish-Czech-German border areas, the objectives and priorities of tourist policy of the three countries have to be observed and respected. The article presents basic assumptions concerning Polish, Czech and German tourist policy as well as conclusions indicating areas for mutual cooperation in the sphere of tourism in the discussed region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 13-25